(untitled) (World Science, 2020)
The article is devoted to the development of international cooperation in the field of sports. The author studies the main factors that influenced the formation of cooperation in this direction and identifies the main stages in its development. The author considers the development of international sports law not only as a branch of law, but also as a branch of science and academic discipline.